X(x-1)(x-2)(x-3)=24 с объяснением, .

Oleg009988 Oleg009988    2   29.08.2019 01:00    1

Ответы
lefuxetube lefuxetube  06.10.2020 01:43
X(x-3)(x-1)(x-2)-24=0
 (x^2-3x)(x^2-3x+2)-24=0
   x²-3x=t
     t(t+2)-24=0
    t²+2t-24=0
   D=4+4*24=100=10²
 t=(-2+10)/2=4                                                        t=(-2-10)/2=-6
 x²-3x=4                                                                  x²-3x=-6
 x²-3x-4=0                                                               x²-3x+6=0
D=9+16=25                                                            D=9-4*6<0        
x=(3+5)/2=4     x=(3-5)/2=-1                                     x∈∅

ответ: x=4; x=-1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра